RICHNESS OF EUGLENOPHYTA IN YARINACOCHA LAGOON (PUCALLPA, UCAYALI), INCLUDING NEW RECORDS FOR PERU - MENDOZA-CARBAJAL, Leonardo Humberto (2023)
The present study aimed to describe the richness of the Phylum Euglenophyta associated with the dry season in Yarinacocha Lake, Pucallpa, Peru, in 2022. The research was developed in 8 sampling stations located within the lake. The methods of collection, identification and analysis of the biological community under study were conducted following the guidelines established by Ortega et al. (2014).  A total of 22 taxa were reported as new records for Peru. The euglenoid community was mainly composed of 1 order (Euglenales), 2 families (Euglenaceae and Phacaceae) and 6 genera (Euglena, Euglenaformis, Strombomonas, Trachelomonas, Lepocinclis and Phacus). The highest species richness was found in the station near the “Nueva Luz de Fátima '' settlement, while the lowest was recorded in front of the restaurant "La Jungla Ecolodge'' and San Juan port. The information provided in this study can be used as a baseline for future research concerning phytoplankton communities from Yarinacocha and its potential value as a bioindicator.